2010
DOI: 10.1007/s10754-010-9077-z
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug coverage among elderly and disabled Americans: can Medicare—Part D reduce inequities in access?

Abstract: This paper explores the determinants of demand for prescription drug coverage among the elderly population in the United States, using data from the Medical Expenditure Panel Survey (MEPS) and seeks to analyse the impact that the Medicare prescription drug coverage bill (Medicare-Part D) has on Medicare beneficiaries. The results indicate that individuals who are Hispanic, black, or of another race or ethnicity, over the age of 74, not married, in poor health, fall into the low- to middle-income brackets, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 1998, the Women’s Health and Cancer Rights Act (WHCRA) passed, mandating that insurance companies provide coverage for postmastectomy breast reconstruction (PBR) . Although initial studies questioned the WHCRA’s effectiveness, the legislation was found to increase the rate of PBR .…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, the Women’s Health and Cancer Rights Act (WHCRA) passed, mandating that insurance companies provide coverage for postmastectomy breast reconstruction (PBR) . Although initial studies questioned the WHCRA’s effectiveness, the legislation was found to increase the rate of PBR .…”
Section: Introductionmentioning
confidence: 99%
“…During the period of these authors' data, telehealth, which is associated with equity issues, [7] was not nearly as pervasive as it is today [8]. Additionally, the authors did not include Medicare Part D. Uptake of prescription drug coverage through Medicare Part D has been found associated with individuals demographics [9]. Additional analyses including these data could reveal opportunities to control expenditure growth without exacerbating inequities.…”
mentioning
confidence: 99%